Magic in the moonlight [videorecording (DVD)] - Allen, Woody, 1935-; Atkins, Eileen, 1934-; Firth, Colin, 1960-; Harden, Marcia Gay (Sony Pictures Home Entertainment, 2014)
Set in the 1920s, Stanley, an Englishman posing as an Asian magician, attempts to debunk fake spiritualists. He then travels to the south of France to unmask a supposed medium named Sophie as a good-looking fake, but he ends up falling for her real-world charms instead.